Fragmentación del empresariado en la época de la industrialización por sustitución de importaciones (ISI) en la Argentina: una aproximación desde el estudio de la red corporativa (1954-1970) - Lluch, Andrea (2012)
This article investigates the behavior and cohesion of the Argentine business elite during the period of import substitution industrialization (ISI) analyzing the interlocking directorates between 1954 and 1970-1971. This study provides the first relational map of large companies and banks in Argentina during the ISI period applying the social network analysis method. In this work we argue that the corporate network in Argentina during the ISI period was characterized by a high level of fragmentation. If interlocking directorates can be considered an expression of the cohesion of the corporate elite, our findings show the limited joint capacity of the corporate network to coordinate economic and business activities. This article also posits that the cohesion of the boards’ network declined between 1954 and 1970. A change in large companies’ ownership structure drove a shift in the interlocking directorates. A second factor explaining this change was a context characterized by frequent changes in economic policy, strong distribution clashes, and severe macroeconomic and institutional volatility. This research indicates that, in a setting where long-term planning proved difficult, board interlocking became less strategically significant as a business coordination mechanism.